2018
DOI: 10.11604/pamj.2018.29.73.14399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding stigma as a barrier to accessing cancer treatment in South Africa: implications for public health campaigns

Abstract: IntroductionCancer contributes to significant illness burden in South Africa, with delayed diagnosis resulting from limited knowledge of cancer, lack of biomedical treatment and stigma. This study examines ways in which people are identified as having cancer through perspectives of traditional healing or the biomedical model. Additionally, we sought to understand the stigma associated with cancer, including stereotypes, anticipated discrimination and coping styles.MethodsLivestrong Foundation conducted 11 semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…The findings were similar to those in our study, with women worrying that being labeled a cancer patient would lead to further social isolation. Interestingly, these studies revealed a fear of change in healthcare workers' behaviorstigmatization, lack of interest in their case if it was judged fatalthat was not expressed in our study, suggesting that trust between women and caregivers may reduce this stigma [33][34][35]. Deepening the understanding of the relationship between women and caregivers through further studies would help to identify factors that could shape a trusting relationship and foster screening strategy implementation.…”
Section: Discussionmentioning
confidence: 72%
“…The findings were similar to those in our study, with women worrying that being labeled a cancer patient would lead to further social isolation. Interestingly, these studies revealed a fear of change in healthcare workers' behaviorstigmatization, lack of interest in their case if it was judged fatalthat was not expressed in our study, suggesting that trust between women and caregivers may reduce this stigma [33][34][35]. Deepening the understanding of the relationship between women and caregivers through further studies would help to identify factors that could shape a trusting relationship and foster screening strategy implementation.…”
Section: Discussionmentioning
confidence: 72%
“…Lack of awareness has been reported as a barrier to cervical cancer screening uptake in low-income settings [ 23 ]. A South African study reported the importance of community outreach cancer education interventions involving traditional healers, churches and the youths to address stigma and other social ills associated with cervical cancer [ 11 ]. Researchers in the USA reported that collaboration of nations, international organizations and industry to develop and roll out workshops, courses and exchange programmes were key to improving health care knowledge and skills about cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Geographical distances and cultural barriers were also cited as impediments to access and uptake of recommended diagnostic and treatment services for cervical cancer [ 10 ]. In South Africa, a recent study reported limited knowledge of cancer, lack of biomedical treatment and stigma as barriers to linkages to treatment and care by women with cervical cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer can be curable when the patient presents early, but once it is advanced the chances of cure is slime. We have got to educate the public to get over the stigma of the disease, seek treatment and not to be shy about it [10]. Prostate cancer is typically a disease that is ignored at the early stage most especially when it is asymptomatic and most men may not present early either for lack of awareness or they see it as a form of social embarrassment, which is often detrimental to their health and quality of life [11,12].…”
Section: Realization Of the I-125 Brachytherapy Proceduresmentioning
confidence: 99%